Breaking the cycle: should we target inflammation, fibrosis, or both? - Baxter, Sarah K.; Irizarry-Caro, Ricardo A.; Vander Heiden, Jason A.; Arron, Joseph R. (Frontiers in Immunology, 2025)
Left unchecked, many chronic inflammatory and autoimmune diseases lead to fibrosis, which can ultimately irreversibly compromise tissue and organ function. A key question for therapeutic discovery and development is whether it is preferable to target inflammation, fibrosis, or both; and in which tissues, organs, diseases, or subsets of patients is a particular therapeutic strategy most relevant? In recent years, clinical and translational studies of human interstitial lung disease tissue and targeted molecular and cellular therapies have yielded mechanistic insights into the interplay between unchecked inflammation and pathological fibrogenesis. Molecular and proteomic technologies have implicated aspects of both innate and adaptive immunity in fibrogenesis, e.g., the presence of a stereotypical population of fibrosis-associated macrophages, recruitment of immune cells by inflammatory fibroblasts, and lymphoid aggregates with B cells producing tissue-specific autoantibodies. In this Perspective, we will consider indications that present with inflammation and/or fibrosis in lung tissue, including systemic sclerosis (SSc), idiopathic pulmonary fibrosis (IPF), and rheumatoid arthritis (RA), in the context of clinical and translational data from molecular interventions targeting cytokine pathways and B lymphocytes. The effects of these interventions on clinical, functional, cellular, and molecular outcomes have started to untangle the mechanistic relationships between inflammation and fibrosis in human diseases, and may illuminate a path toward improved strategies to restore tissue homeostasis and preserve or improve functional outcomes in the future. However, substantially more granular clinical outcomes, biomarker data, and assay standardization across interventions and diagnoses are needed to effectively link therapeutic targets, disease pathophysiology, and clinical benefit.